2017
DOI: 10.22581/muet1982.1703.18
|View full text |Cite
|
Sign up to set email alerts
|

Application of Lean Agile Resilient Green Paradigm Framework on China Pakistan Economic Corridor: A Case Study

Abstract: China has recently emerged as the technological and economic giant and an attractive place for investment for MCNs (Multi-National Companies). Many of the high ranked MNC's have shifted their production facilities to China due to low production cost.Finished products are transported through sea routes passing through Singapore and Sri Lanka, to different Middle Eastern, European and American countries. This major transition has lead to complete transformation of the global SC (Supply Chain);which resulted into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Azevedo et al (2016) demonstrated LARG index can be as a benchmarking tool for improving the leanness, agility, resilience and greenness of the automotive supply chain. Azfar et al (2017) showed that the application of Lean Agile Resilient Green Paradigms Framework Can play an effective role on China Pakistan Economic Corridor. Ruiz-Benitez et al (2017) showed that the combination of lean, green, and resilient supply chain management there are environmental benefits in the aerospace sector.…”
Section: Theoretical Foundations and Literaturementioning
confidence: 99%
“…Azevedo et al (2016) demonstrated LARG index can be as a benchmarking tool for improving the leanness, agility, resilience and greenness of the automotive supply chain. Azfar et al (2017) showed that the application of Lean Agile Resilient Green Paradigms Framework Can play an effective role on China Pakistan Economic Corridor. Ruiz-Benitez et al (2017) showed that the combination of lean, green, and resilient supply chain management there are environmental benefits in the aerospace sector.…”
Section: Theoretical Foundations and Literaturementioning
confidence: 99%
“…Data from a survey of Taiwanese coordinating groups was used for the demonstration. GSCM has taken a proactive approach to improving the natural presentation of cycles and objects by ecological principles (Azfar et al, 2017). This study examined approaches to ensure the consistency of examination of the factors that influence GSCM implementation and enactment.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…They were a technology that aimed to shorten lead times, boost productivity, and eliminate waste by giving users more control over the supply chain. The Toyota Production System (TPS), with its Lean Philosophy, was popular (Azfar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of particular interest to mention the work of Azfar et al [48] because it deals with the evolution of a supply chain in relation to the evolution of the main transport system on which it operates. In this sense, it is the closest paper to our study of the LARG paradigm for a railway infrastructure.…”
Section: Larg Paradigm In the Industrymentioning
confidence: 99%